2023
DOI: 10.3389/fcvm.2023.1105507
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative optimization of cardiac valve patients’ expectations: Study protocol of the randomized controlled ValvEx-trial

Abstract: IntroductionComplete recovery after surgery depends on psychological factors such as preoperative information, expectations, and surgery-associated anxiety. Prior studies have shown that even a short preoperative psychological intervention aiming at optimized expectations (EXPECT) can improve postoperative outcomes in coronary artery bypass patients. However, this intervention may benefit only a small subgroup of heart surgery patients since implementing preoperative psychological interventions into the daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, patients with moderate to severe anxiety before cardiac surgery present with higher postoperative pain scores and a significantly increased need for intra- and postoperative analgesia, according to Muhammad Kashif et al ( 95 ). SAVR or TAVR, though, could aid in reducing anxiety among elderly patients with AS ( 89 , 96 ) and increasing confidence in their bodily states ( 16 , 97 ), while CR could aid in improving depressive states ( 18 , 98 100 ). Screening for psychological disorders should be incorporated into preoperative risk stratification ( 101 ), and future research must determine whether interventions to treat psychological disorders preoperatively or postoperatively can improve outcomes.…”
Section: Factors Influencing Avr Prognoses That Require Consideration...mentioning
confidence: 99%
“…In addition, patients with moderate to severe anxiety before cardiac surgery present with higher postoperative pain scores and a significantly increased need for intra- and postoperative analgesia, according to Muhammad Kashif et al ( 95 ). SAVR or TAVR, though, could aid in reducing anxiety among elderly patients with AS ( 89 , 96 ) and increasing confidence in their bodily states ( 16 , 97 ), while CR could aid in improving depressive states ( 18 , 98 100 ). Screening for psychological disorders should be incorporated into preoperative risk stratification ( 101 ), and future research must determine whether interventions to treat psychological disorders preoperatively or postoperatively can improve outcomes.…”
Section: Factors Influencing Avr Prognoses That Require Consideration...mentioning
confidence: 99%
“…This influence remains consistent regardless of the patient's medical condition or the type of surgical procedure ( 3 ). Negative expectations are associated with more complications, lower quality of life, higher illness-related disability, depressive symptoms, and prolonged inability to work ( 4 , 5 ). Interventions to optimize patients' expectations before undergoing heart surgery have been developed in the past ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Negative expectations are associated with more complications, lower quality of life, higher illness-related disability, depressive symptoms, and prolonged inability to work (4,5). Interventions to optimize patients' expectations before undergoing heart surgery have been developed in the past (5)(6)(7). Former studies showed an association between expectation-focused interventions and a faster recovery, including a reduced hospital stay and quicker return to work (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%